Comparison of effect and safety of phacoemulsification surgery performed by resident and attending physicians - Wu, Siteng; Yao, Dongwei; Hua, Shanshan; Li, Xiangzhe; Shi, Yan (Frontiers in Medicine, 2024)
Aim: The objective of this study is to compare the effect and safety of phacoemulsification surgery performed by resident and attending physicians. Methods: This was a retrospective study. Eyes with cataract who underwent phacoemulsification surgery at the First Affiliated Hospital of Ningbo University between January 2021 and December 2023 were reviewed. All the patients were followed up for at least 12 months and were divided into two groups according to the surgery performer. SPSS was used to analyze data, considering P<0.05 significant. Results: Overall, 316 patients with cataract in group 1 (surgery performed by resident physician, n=181) and group 2 (surgery performed by attending physician, n=135) were reviewed. There were no statistically significant differences in patient demographics variables and cataract grade between the groups. The resident surgeon used more cumulative dissipate energy (15.00 ± 7.25 VS 10.83 ± 6.52, p＜0.001) and operation time (20.46 ± 5.69 VS 12.59 ± 4.61 min, p＜0.001)to complete the surgery. Also, the ECL in group 1 was higher (14.87 ± 5.00 VS 10.77 ± 4.46, p＜0.001). The eyes had significant visual improvement in both groups postoperatively (p<0.05), but at the 12-month follow-up, eyes in group 2 had better best-corrected visual acuity (0.10 (0.00, 0.22) vs 0.10 (0.10, 0.22) logMAR, p=0.039). Except for month 1, the intraocular pressure was no statistical difference in group 1 and group 2 (14.65 ± 2.52 vs 15.30 ± 2.34 mmHg, p=0.019). Cases in group 1 were more likely to undergo intraoperative and postoperative complications (37 vs 14, p=0.031), including cornea edema (p=0.025), capsule tear (p=0.044), and posterior capsular opacification (p=0.027). Conclusion: The effect of phacoemulsification surgery performed by the resident physician is satisfying, but compared to the attending physician, the higher probability of complications should be paid more attention.